Lactate response to short term exercise with elevated starting levels - Beneke, R.; Wittekind, A.; Mühling, M.; Bleif, I.; Leithäuser, R. (European Journal of Applied Physiology, 2010)
A model that describes the blood lactate concentration (BLC) dynamics [BLC(t)] of a Wingate Anaerobic Test (WAnT) as a function of (a) BLC at the start of exercise (BLC0), (b) extra-vascular increase in lactate (A), (c) two corresponding velocity constants of appearance (k 1) and disappearance (k 2) of lactate into and out of the blood requires that BLC0 is equal to resting BLC (BLCrest). We developed a model that considers an elevated BLC0. 19 males performed WAnTs with warm-ups increasing (p < 0.001) BLC0. The goodness of each individual fit improved (p < 0.05) if the difference between BLCrest and BLC0 (delta BLC) was higher than 1.0 mmol l-1. All differences between old and new model (p < 0.05) in A, k 1 and k 2 were interrelated with and increased with delta BLC (p < 0.05). The new model well describes BLC(t) and prevents substantial errors concerning lactate generation and dynamics if BLC0 is elevated by more than 1.0 mmol l-1.